A Novel Algorithm for the Assessment of Blood-Brain Barrier Permeability Suggests That Brain Topical Application of Endothelin-1 Does Not Cause Early Opening of the Barrier in Rats. (27th February 2011) - Jorks, D.; Milakara, D.; Alam, M.; Kang, E. J.; Major, S.; Friedman, A.; Dreier, J. P.
Abstract : There are a number of different experimental methods for ex vivo assessment of blood-brain barrier (BBB) opening based on Evans blue dye extravasation. However, these methods require many different steps to prepare the brain and need special equipment for quantification. We here report a novel, simple, and fast semiquantitative algorithm to assess BBB integrity ex vivo . The method is particularly suitable for cranial window experiments, since it keeps the spatial information about where the BBB opened. We validated the algorithm using sham controls and the established model of brain topical application of the bile salt dehydrocholate for early BBB disruption. We then studied spreading depolarizations in the presence and the absence of the vasoconstrictor endothelin-1 and found no evidence of early BBB opening (three-hour time window). The algorithm can be used, for example, to assess BBB permeability ex vivo in combination with dynamic in vivo studies of BBB opening.